2008
DOI: 10.1093/annonc/mdm585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum HER2 extracellular domain in early breast cancer patients: correlation with clinicopathological parameters and survival

Abstract: Background:We explored the correlation between serum human epidermal growth factor receptor-2 (HER2) extracellular domain (ECD) and tissue HER2 status, their relationship with clinicopathological parameters and their impact on disease-free survival (DFS) and overall survival in early breast cancer patients. High serum HER2 ECD levels ( ‡15 ng/ml) were reported in 23 patients (9.0%) and HER2-positive status in tumor tissue was observed in 42 patients (16.4%) with a concordance of 87.1%. High HER2 ECD levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
78
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 27 publications
14
78
1
3
Order By: Relevance
“…and with 0/1? by IHC; there was a high statistical correlation between serum HER2 ECD levels and tissue HER2 status (P = 0.001, R = 0.392), which is in accordance with the results from some studies with comparable large sample sizes (Molina et al 2003; Ludovini et al 2008;Sugano et al 2000), which might indicate that when the tissue HER2 status was 2? and FISH based on tumor specimen that could not be available, serum HER2 ECD levels might aid to assess tumor HER2 status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…and with 0/1? by IHC; there was a high statistical correlation between serum HER2 ECD levels and tissue HER2 status (P = 0.001, R = 0.392), which is in accordance with the results from some studies with comparable large sample sizes (Molina et al 2003; Ludovini et al 2008;Sugano et al 2000), which might indicate that when the tissue HER2 status was 2? and FISH based on tumor specimen that could not be available, serum HER2 ECD levels might aid to assess tumor HER2 status.…”
Section: Discussionsupporting
confidence: 89%
“…However, the prognostic value of serum HER2 ECD in primary operable breast cancer was still controversial. Two studies observed that HER2 ECD was an independent prognostic factor in early breast cancer (Molina et al 2003;Ludovini et al 2008), but other studies did not support this (Quaranta et al 2006;Molina et al 2010). To further investigate its prognostic value in Chinese population, we evaluated the relationship between serum HER2 ECD levels and tissue HER2 status, their association between clinicopathological characteristics, and their impacts on DFS and OS in Chinese primary operable breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…First, using the cutoff value, 15 ng/ml, which is most widely used in breast cancer (7,9,10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), the evaluable 100 patients were stratified into serum HER2-positive (≥15 ng/ml) or -negative (<15 ng/ml) groups, as well as. Sensitivity and specificity were defined as the proportion of the true-positive (TP)/true-negative (TN) patients among tissue HER2-positive/negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended that a 37 g/l serum HER-2 ECD cutoff be used, which can achieve 95% specificity but low sensitivity for HER-2-positive status determined on primary tumors [229]. Studies of breast cancer prognosis based on the serum ECD test have been conflicting, with some finding significant correlation [116] and others finding weak or no correlation [230]. In 22 published studies on 4,088 patients, 16 (73%) studies involving 3,458 (85%) of the patients reported a significant correlation of serum HER-2 protein levels with disease recurrence, metastasis, or shorter survival [231][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246][247].…”
Section: Tissue and Serum Enzyme-linked Immunosorbentmentioning
confidence: 99%